Cascaded emission of single photons from the biexciton in monolayered WSe2 - Yu-Ming He (Nature Portfolio, 2016)
Atomically thin transition metal dichalcogenides constitute an ideal platform to investigate solid state excitonic effects. Here, the authors provide experimental evidence of a localized biexciton in a monolayer of WSe2, which induces an emission cascade of single photons.